2012
DOI: 10.1038/nrclinonc.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Exercise rehabilitation in patients with cancer

Abstract: Emerging evidence indicates that patients with cancer have considerable impairments in cardiorespiratory fitness, which is likely to be a result of the direct toxic effects of anticancer therapy as well as the indirect consequences secondary to therapy (for example, deconditioning). This reduced cardiorespiratory fitness is associated with heightened symptoms, functional dependence, and possibly with an increased risk of cardiovascular morbidity and mortality. Current understanding of the complex interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 60 publications
3
107
1
3
Order By: Relevance
“…This model is important as it conceptualizes the importance of maintaining and improving physical fitness levels in persons with MS. Physical fitness might provide a form of "physiological reserve" that is protective of disease consequences and worsening of MS and this is consistent with other literatures such as cancer [9].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…This model is important as it conceptualizes the importance of maintaining and improving physical fitness levels in persons with MS. Physical fitness might provide a form of "physiological reserve" that is protective of disease consequences and worsening of MS and this is consistent with other literatures such as cancer [9].…”
supporting
confidence: 77%
“…This model is important as it conceptualizes the importance of maintaining and improving physical fitness levels in persons with MS. Physical fitness might provide a form of "physiological reserve" that is protective of disease consequences and worsening of MS and this is consistent with other literatures such as cancer [9].To that end, this paper provides a comprehensive review of research on physical fitness in persons with MS. We begin by defining physical fitness and its domains as well as differentiating it from physical activity. We then present research on physiological deconditioning (i.e., detraining that manifests as a reduction in domains of physical work capacity or fitness) in persons with MS as well as evidence on the association between markers of physical fitness and consequences of MS. We lastly review research regarding the effects of exercise training on physical fitness and consequences of MS, and conclude with recently developed exercise recommendations for improving physical fitness.…”
supporting
confidence: 59%
“…23 A decrease in D LCO is a common finding when performing lung function tests during or after chemotherapy. Lakoski et al 9 reviewed the effects of chemotherapeutic agents on components of oxygen transport and suggested that platinumbased chemotherapy impacts its pulmonary component, presumably by diminishing diffusion capacity. Pulmonary toxicity was also reported for taxanes and gemcitabine.…”
Section: Diffusion Capacitymentioning
confidence: 99%
“…8 The effects of other classes of chemotherapeutic agents and the effects of chemotherapy in general on other components of oxygen delivery and consumption are still poorly explored. 9 Despite such serious adverse effects, survival is improved with preoperative neoadjuvant chemotherapy (NAC) followed by surgery, compared with surgery alone. [10][11][12] By reducing the tumor burden and downgrading the tumor stage, NAC facilitates surgical resection and may improve long-term outcome by eradicating micrometastases.…”
Section: Introductionmentioning
confidence: 99%
“…Many anticancer therapies cause unique and varying degrees of injury to the cardiovascular system (i.e., pulmonary-vascular/blood-skeletal muscle axis) [50]. For example, radiation and certain forms of systemic therapy (e.g., chemotherapy, molecularly targeted therapies) can cause pulmonary dysfunction, anemia, endothelial dysfunction and pulmonary/systemic arterial stiffness as well as skeletal muscle dysfunction [11,12,[51][52][53]. These direct insults occur in conjunction with 'indirect' lifestyle perturbations (e.g., physical inactivity) that synergistically cause marked impairments in cardiovascular reserve capacity [54].…”
Section: Current State Of Detection Of Cardiotoxicitymentioning
confidence: 99%